Losing our medicinal trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Ms Theresina Chimombe of Westgate, Zimbabwe, reminds us that 'deterioration of the environment is a killer to our health because some precious medicinal bushes are being destroyed. In the past, local folks knew the importance of our local wild...